THE POSSIBILITY OF TREATING PATIENTS WITH GASTRIC CANCER WITH METASTASES TO THE BONES OF THE SKELETON - N. V. Rasulova; D. T. Arybzhanov; F. Z. Dzhalalov; Kyeong Hwan Kim (Креативная хирургия и онкология)
The results of treatment of 14 patients with gastric cancer with metastases to the bones of the skeleton  were analized, which was conducted by the stabilization of metastatic spine vertebroplasty, systemic  radionuclide therapy with  samarium-153 oksabifor and  intravenous infusion  by Zolendronic  acid 4 mg 1 time in 28 days. When applying this method decreased by stabilizing vertebral  pain occurred in the first 12 hours after vertebroplasty (cf. value 4.8±1,2 hours, from 30 minutes to 12 hours), the average pain intensity decreased to 4.5 ±0,6 (from 2 to 6). After the treatment of bone  metastases with samarium-153 oksa bifor,  pain intensity  decreased by 3,9 ± 0,3 days (range from 2 to 6) and reached the level of 0,9 ± 0,5 (from 0 to 2). Value pain scores before and after treatment was significantly different, and was P <0,0001. Thus,  the  combination of  vertebroplasty, radionuclide therapy  with  samarium-153 oksabifor and  systemic  therapy with bisphosphonates (Zolendronic acid)  in patients with gastric  cancer  with bone  metastases can be treated in the  presence or threat of vertebral fractures, which gives an opportunity to expand the  indications for palliative radionuclide therapy and improve efficiency treatment of severe category of patients with multiple bone metastases and pain. The proposed approach allows us to quickly achieve durable  and pronounced reduction in pain intensity, significantly  reduce the need for analgesics.